Scientific Information of Higher Education: Analysis of Scientific Information Needs of Academics of The Stikes Gunung Maria : Informasi Ilmiah Sekolah Tinggi: Analisis Kebutuhan Informasi Ilmiah Akademisi Stikes Gunung Maria - Tinangon, Hellena Anastasia; Fahriyah; Prakoso, Bambang (Universitas Airlangga, 2025)
Background of the study: Improving the quality of education and research in higher education institutions requires a deep understanding of the different information needs of students, lecturers, and educational staff. Lecturers need information to fulfill their learning materials and support their performance. Students need reading material to support their lectures. Educational staff have information needs to complete the work tasks they are responsible for. Purpose: This research aims to conduct an analysis of scientific information needs at the Gunung Maria Tomohon College of Health Science. Methods: Descriptive research method with a qualitative approach. The sampling technique chosen was Non-Probability Sampling, determining informants using purposive sampling, namely 8 leaders including lectures, 1 educational staff, and 3 students. Data collection techniques through observation, interviews and documentation. The data analysis technique uses the Miles Huberman Model, namely data reduction, data display, data verification and drawing conclusions. Finding: The research results show that lecturers need resources such as text books, scientific journals, lecture materials, the latest information, access to scientific journals and other literature to support the teaching process, research and produce scientific publications. Educational staff need information related to academic administration, class schedules, student services, literature that supports skills development, and seminar information. Students need a collection of printed books, journals and other materials to support completing coursework, and easy access to digital resources and research to support writing their final assignments. The need for scientific information cannot be fully provided by libraries, academics still need internet access to Google Scholar and other institutional databases. Conclusion:The need for the Gunung Maria Tomohon Library to provide an e_repository information system to collect local content collections for academics and provide e_repository services to meet the scientific information needs of lecturers, education staff and students. Keywords: Scientific Information Needs; Local Content; Higher Education Informasi Ilmiah Sekolah Tinggi: Analisis Kebutuhan Informasi Ilmiah Akademisi Stikes Gunung Maria ABSTRAK Latar Belakang: Perbedaan kebutuhan informasi antara mahasiswa, lecturers, dan tenaga kependidikan perlu pemahaman khusus dalam upaya peningkatan aspek kualitas pengajaran dan penelitian di pendidikan tinggi. Kebutuhan informasi mahasiswa beragam jenis bacaan guna mendukung perkuliahannya. Lecturers memerlukan bahan bacaan untuk menunjang kinerja dan kegiatan tri darmanya. Sedangkan kebutuhan informasi tenaga kependidikan guna penyelesaian tugas yang menjadi tanggung jawab pekerjaannya. Tujuan: Riset ini bertujuan melakukan analisis terhadap kebutuhan informasi ilmiah di Manado Sulawesi Utara tepatnya pada Sekolah Tinggi Ilmu Kesehatan (STIKes) Gunung Maria Tomohon. Metode: Metode penelitian dengan pendekatan deskriptif kualitatif. Non-Probability Sampling dipilih sebagai teknik sampling, penentuan informan dengan purposive sampling, yaitu 8 orang dosen, 3 orang mahasiswa, dan 1 orang tenaga kependidikan (tendik). Dokumentasi, observasi, dan wawancara dilakukan dalam rangka pengumpulan data. Teknik analisa data yaitu reduksi data, lalu display data, verifikasi data, kemudian penarikan kesimpulan. Temuan: Hasil penelitian diketahui bahwa lecturer memerlukan informasi ilmiah seperti textbooks, jurnal ilmiah, bahan perkuliahan, akses ke jurnal ilmiah, informasi pendidikan terbaru, dan literatur lainnya untuk mendukung proses riset, pengajaran, dan publikasi ilmiah. Mahasiswa membutuhkan koleksi cetak buku, jurnal, dan materi lainnya, kemudahan akses ke sumber daya digital, menunjang penyelesaian tugas kuliah, dan penelitian untuk penyelesaian tugas akhirnya. Tenaga kependidikan membutuhkan informasi tentang administrasi akademik, layanan mahasiswa, jadwal kuliah, berbagai literatur untuk pengembangan keterampilan, dan akses ke layanan akademik, kemahasiswaan, informasi seminar dan pelatihan. Unit Perpustakaan belum sepenuhnya dapat menyediakan kebutuhan informasi ilmiah bagi sivitas akademika. Mereka membutuhkan akses internet seperti google scholar serta pangkalan data instansi lain. Kesimpulan: Perlunya ketersediaan sistem informasi e-repository di Perpustakaan STIKes Gunung Maria Tomohon untuk mengumpulkan koleksi local content sivitas akademika dan memberikan layanan e-repository guna memenuhi kebutuhan informasi ilmiah lecturers, mahasiswa, dan tenaga kependidikan. Kata Kunci: Kebutuhan Informasi; Informasi Ilmiah; Local Content; Perguruan Tinggi.